Community based pilot study of diagnostic paths to the gluten free diet - Stevenson, Joan C; Rankin-Sunter, Kelle; Maki, Crystal; Bruna, Sean; Mosher, M. J; Barrett, Christopher E (International journal of celiac disease, 2015)
Wheat consumption is increasing worldwide and also increasing is the frequency of celiac disease (CeD), a pathological response to wheat protein (gluten) in genetically susceptible individuals. Non-celiac gluten sensitivity (NCGS) is another, less studied wheat-induced pathology. The treatment for both is a gluten-free diet (GFD). More individuals choose the diet than predicted by the epidemiological 1-2% prevalence. A preliminary survey by questionnaire asked members and attendees of the local gluten information group (GIG) meetings and functions about their diagnostic experiences and symptom levels in order understand the increased demand for gluten-free foods. Same-aged and -sex friends participated as a comparative “control”. Mixed methods were used including content analyses of prose narratives and independent and paired t tests of symptom levels measured with Likert scales. This convenience sample, surveyed in 2011-2012, is mostly female (54 F, 5 M) with an average age of 54.6 ± 2.0 years. Most participants consulted medical professionals with mean time to diagnosis of 7 years determined mostly from “classic” presenting symptoms. Negative biopsies or blood tests and atypical symptoms that overlap other conditions delayed diagnosis. There were 43 and 16 participants with CeD and NCGS, respectively differing little in symptom levels. Self-diagnosis and use of naturopaths account for some of the “excess” individuals. General practitioners should be encouraged to get additional nutrition training and to discuss with patients dietary choices that support wellness and minimize the risk for pathological immune responses. Patients with CeD particularly need support and follow-up in the transition to a GFD.
Keywords: autoimunitní tyreoiditida; Diet, Gluten-Free; Surveys and Questionnaires; Humans; diferenciální diagnóza; Signs and Symptoms; lidé středního věku; Wheat Hypersensitivity; imunitní systém; Chronic Disease; Female; dospělí; Patient Education as Topic; výsledek terapie; Delayed Diagnosis; Immune System; Diagnosis, Differential; lidé; jídelníček; Fatigue; alergie na pšenici; pilotní projekty; Pilot Projects; průzkumy a dotazníky; Adult; Thyroiditis, Autoimmune; příznaky a symptomy; celiakie; bezlepková dieta; ženské pohlaví; Male; Middle Aged; chronická nemoc; Treatment Outcome; atypické symptomy; únava; Celiac Disease; opožděná diagnóza; Menu Planning; vzdělávání pacientů jako téma; neceliakální glutenová senzitivita; mužské pohlaví